Traditional male circumcision : Balancing cultural rights and the prevention of serious, avoidable harm. - Behrens, K G (My University, 2014)
The right to participate in cultural practices should be protected. However, it is a limited right, and does not entail a right to activities that cause serious and avoidable harms. I argue that the harms currently resulting from traditional circumcision are very serious, and that we have an obligation to ensure that the practice is effectively regulated so as to minimise them
PK
Keywords: Circumcision, male; Circumcision, male/adverse effects; Medicine, African Traditional